Xosé Carlos ARIAS y Antón COSTAS. La nueva piel del capitalismo. Galaxia Gutemberg, Barcelona, 2016 - Bastos Boubeta, Miguel Anxo (Gestión y Análisis de Políticas Públicas, 2017)
La nueva piel del capitalismo.